2017
DOI: 10.1088/2050-6120/aa5e57
|View full text |Cite
|
Sign up to set email alerts
|

A new fluorescence turn-on nanobiosensor for the detection of micro-RNA-21 based on a DNAgold nanocluster

Abstract: In this study, DNA/gold nanoclusters (AuNCs) were used to develop an AuNC-based turn-on fluorescence probe for the analysis of mi-RNA-21, which is a potential screening biomarker for cancer detection. AuNCs on a DNA scaffold were prepared through a one-pot wet-chemical route and evaluated by transmission electron microscopy and dynamic light scattering. Experiments revealed that the fluorescence intensity of the DNA-AuNCs showed a gradual increase with the addition of the target species in a concentration rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…These miRNA electrochemical nanobiosensors can be implied for the quantification of different miRNAs for detection of different diseases, such as lung cancer [31], breast cancer [24], gastric cancer [32], glioma [33], Alzheimer [34], etc. But, beside the electrochemical methods, there are other types of high-performance nanobiosensors such as fluorescent methods which can be applied for miRNA quantification and responded very well [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…These miRNA electrochemical nanobiosensors can be implied for the quantification of different miRNAs for detection of different diseases, such as lung cancer [31], breast cancer [24], gastric cancer [32], glioma [33], Alzheimer [34], etc. But, beside the electrochemical methods, there are other types of high-performance nanobiosensors such as fluorescent methods which can be applied for miRNA quantification and responded very well [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Hosseini et al showed a fluorescence turn-on biosensor for the detection of microRNA [29]. AuNCs were synthesized by templated DNA, containing the complementary sequence of target microRNA and two cytosine rich sequence fragments at the 3 and 5 ends.…”
Section: Auncs-based Fluorescent Sensors For Detection Of Dna and Mic...mentioning
confidence: 99%
“…Gold nanoclusters (AuNCs) have become a hot topic for the current nanoscience research because they have a broad application prospect in many fields including sensing, biological imaging, catalysis, and electronic devices. AuNCs typically comprise several to hundreds of atoms with sizes approaching the Fermi wavelength of the conduction electrons, leading to the emergence of unexpected strong photoluminescence. , As a new kind of fluorescent nanomaterials, AuNCs have many distinct features such as simple synthesis, easy modification, good water dispersibility, low toxicity, good compatibility, and excellent stability. Based on their unique optical properties, AuNCs as robust and promising fluorescent probes have been frequently used for the determination of numerous analytes like ions, , small molecules, , enzymes, nucleic acids, cancer cells, and so on. However, most of the AuNC-related sensors were fabricated via fluorescence quenching (turn-off), which are comparatively less sensitive than turn-on sensors.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 As a new kind of fluorescent nanomaterials, AuNCs have many distinct features such as simple synthesis, easy modification, good water dispersibility, low toxicity, good compatibility, and excellent stability. Based on their unique optical properties, AuNCs as robust and promising fluorescent probes have been frequently used for the determination of numerous analytes like ions, 18,19 small molecules, 20,21 enzymes, 22−24 nucleic acids, 25 cancer cells, 26 and so on. However, most of the AuNC-related sensors were fabricated via fluorescence quenching (turn-off), which are comparatively less sensitive than turn-on sensors.…”
Section: ■ Introductionmentioning
confidence: 99%